A Paradigm Shift In Foreign Tourist Arrivals – The Imperative For Penang Hill’s Sustainable Growth - Summugam, Sukumaran (2015)
The emergence of tourism industry over the last few decades had tremendously contributed to the continued growth of Penang economy and lately the industry had a deepening diversification to become one of the fastest growing economic sectors in Penang. Tourism is closely linked to development of various tourism products and attractions that encompasses the growing number of new destinations such as the Georgetown Heritage Enclave, 3D Museum, The Butterfly Farm and etc.